Mothers' alexithymia in the context of parental Substance Use Disorder: Which implications for parenting behaviors?. (October 2020) - Porreca, Alessio; De Carli, Pietro; Filippi, Bianca; Parolin, Micol; Simonelli, Alessandra
Abstract: Background: Maternal substance use disorder (SUD) represents a severe risk for caregiving, affecting diverse domains of parenting behaviors, such as sensitivity, structuring, intrusiveness, and hostility. Various studies highlighted that difficulties in parenting behaviors in the context of SUD are exacerbated by the co-occurrence of psychopathological symptoms. A large body of research points out the presence of high rates of alexithymia in individuals with SUD, and some studies provide evidence of an association between this psychopathological aspect and parenting. Nevertheless, no prior research has explored how alexithymic traits could affect quality of parenting behaviors in mothers with SUD. Objective: To investigate the impact of maternal alexithymia on parenting behaviors in mothers with SUD. Methods: Sixty women in residential treatment for SUD and their children participated in the study. The participants were assessed with respect to alexithymia, quality of parenting behaviors, and depressive symptoms. Results: Forty-three percent of the mothers reported the presence of alexithymia. These mothers presented with significantly low scores on sensitivity ( β = -.25, p < .05) and structuring ( β = -.32, p < .05). After controlling for depressive symptomatology, the effect of alexithymia on parenting behaviors remained only for structuring ( β=. 35, p < .05). Conclusions: In the context of SUD, maternal alexithymia significantly impacts the quality of parenting behaviors, specifically structuring, indicating that difficulties in becoming aware of one's own feelings jeopardize the ability to scaffold interactions and set age-appropriate limits in an emotionally attuned way. Clinical implications of the findings are discussed.